Respuesta :

(0, -3) is the answer. Plug all the options into the equation and the only one that works is (O, -3)

Answer:

(C) and (D)

Step-by-step explanation:

The given equation of the circle is:

[tex](x-2)^2+(y+3)^2=4[/tex]

A. Substitute the value of x=2 and y=-4 in the given equation, we have

[tex](2-2)^2+(-4+3)^2=4[/tex]

[tex]1=4[/tex]

which is not possible, thus (2,-4) does not lie in the given equation.

B. Substitute the value of x=2 and y=0 in the given equation, we have

[tex](2-2)^2+(0+3)^2=4[/tex]

[tex]9=4[/tex]

which is not possible, thus (2,0) does not lie in the given equation.

C.Substitute the value of x=0 and y=-3 in the given equation, we have

[tex](0-2)^2+(-3+3)^2=4[/tex]

[tex]4=4[/tex]

which is  possible, thus (0.-3)  lies in the given equation.

D.Substitute the value of x=2 and y=-5 in the given equation, we have

[tex](2-2)^2+(-5+3)^2=4[/tex]

[tex]4=4[/tex]

which is possible, thus (2,-5) lies in the given equation.